2-torsion points on theta divisors. (4th November 2019) - Pareschi, Giuseppe; Salvati Manni, Riccardo
Abstract: In this note we prove a sharp bound for the number of 2-torsion points on a theta divisor and show that this is achieved only in the case of products of elliptic curves. This settles in the affirmative a conjecture of Marcucci and Pirola.